Efficiency of phage therapy in humans: systematic review - N. V. Saperkin; O. V. Kovalishena; D. V. Kvashnina; E. Ruizendaal; R. Scholten (Журнал инфектологии, 2019)
Successful implementation of lytic virulent bacteriophages in clinical practice requires convincing evidence of its safety and efficacy.Design: We searched in CENTRAL, MEDLINE, Embase, and Russian-language literature databases in May 2018. Original articles must fulfill the following eligibility criteria: randomized, controlled trials investigating the effects of phage therapy in people with bacterial infections; at least one patient outcome was reported. Three review authors independently selected, studies, extracted, data, and. assessed, risk of bias. We used, random-effects models for meta-analysis.Participants: adults and. children of both, sexes with bacterial infection, including multi-drug resistant variants, or individuals at risk of infection.Outcomes: recovery or resolution of infection; clinical improvement; change in number of exacerbations; recurrence of infection; quality of life; elimination or load, reduction of a pathogen in an anatomical compartment.Results: We included 13 trials (issued in 1965-2018) including 9 treatment studies and. 4 prevention studies. Overall, eight randomized, trials involved, adults. Five studies addressed skin and soft tissues infections, six studies concerned intestinal infections, one study addressed respiratory tract infection and. one study — ear infection. Across bias domains, 35-90% of trials scored, low risk of bias. Meta-analysis for adverse events attributable to phages and. for wound, healing provided us with pooled relative risks of 0.74 (95% CI 0.68;1.2) and 0.91 (95% CI0.68;1.2) respectively.Conclusions: Beneficial effect of bacteriophages can be demonstrated, and. not refuted. However, our study led. to tentative conclusions. The conduct of well-designed and sufficiently powered, trials would, facilitate registration and. wide accepting of bacteriophage treatment.